The effect of environmental awareness, the role of accountants, and sustainable development on climate change - Meipry Amelia; Sudibyo, Yvonne Augustine (Technium Social Sciences Journal, 2023)
The purpose of this study is to determine the effect of environmental awareness on climate change, to determine the role of accountants in influencing climate change, to determine the effect of sustainable development on climate change. Design/methodology/approach - The method of collecting data and information used in this study uses quantitative methods with Statistical Program for Social Science (SPSS) 24. So that the research instrument used in this study is to ask questions using a questionnaire. This research is a modification of previous research. Findings - The results of this study indicate that environmental awareness has a significant influence on climate change, the role of accountants has a significant influence on climate change, sustainable development has a significant influence on climate change. Practical implications - This research is then used as a guide for researchers who want to make scientific papers or thesis with a title similar to or a variable for research